Third Five Year Plan Programme for 1964-65 Government of Mysore - Planning Commission (Planning Commission, 1964)
The fourth year of the Third Five Year Plan has been reached now. This Volume sets out the programme of development for the year 1964-65. This embodies an attempt to indicate the progress that the State is expected to achieve by the end of the Third year of the Third Plan. The statements appended show the schemewise expenditure incurred in 1961-62, 1962-63 and 1963-64 and the provision made for 1964-65 as also schemewise physical progress for the past three years and the targets set for 1964-65. Each Chapter deals with one Head of Development only.
Planning, Housing and Social Welfare Department Government of Mysore